Development of Predictive Models for Water Budget Simulations of Closed-Basin Lakes: Case Studies of Lakes Azuei and Enriquillo on the Island of Hispaniola - Moknatian, Mahrokh; Piasecki, Michael (CUNY Academic Works, 2021)
The historical water level fluctuations of the two neighboring Caribbean lakes of Azuei (LA) and Enriquillo (LE) on Hispaniola have shown random periods of synchronous and asynchronous behaviors, with both lakes exhibiting independent dynamics despite being exposed to the same climatic forces and being directly next to each other. This paper examines their systems' main drivers and constraints, which are used to develop numerical models for these two lakes. The water balance approach was employed to conceptually model the lakes on an interannual scale and examine the assumptions of surface and subsurface processes. These assumptions were made based on field observations and prior studies. The developed models were optimized and calibrated for 1984 to 2017 and then validated for the period 1972 to 1984 based on the lakes’ observational volume change and volume time series. The models yielded “good” performance, with NSE averaged at 0.7 and RE averaged at 13% for volume change. The performance improved to “very good” for volume simulations, with NSE averaging higher than 0.9 and RE averaging at 1%. The uncertainty analysis showed a p-factor [M1] of 0.73 and an r-factor of 1.7 on average, supporting the reliability and precision of the results. Analyzing the time series of the lakes and quantifying the main elements of the water balance, each lake’s shrinkage and expansion phases were explored, and the drivers of such behavior were identified for each lake. The main drivers of LE’s system are North Atlantic cyclone activities and uncontrolled inter-basin water transfer, and direct rainfall and evaporation to/from its surface. The LA system is mainly controlled by groundwater fluxes in and out of the lake, despite having only small values for its water budget components.